The effect of nanoclay (NC) on mechanical, thermal, and morphological properties of wood plastic composite (WPC) based on recycled polyethylene (rPE) and kenaf fiber - Indok Nuratikah, Nizamudin; Ros Azlinawati, Ramli; Rodziah, Nazlan; Yuen, Mei Lian; Wan Amirah Najwa, Wan Anuar (Springer Nature, 2024)
This development contributes to the effects of nanoclay (NC) on mechanical, thermal, and morphological properties of wood plastic composites (WPC). The WPC was formulated with recycled polyethylene (rPE), kenaf fiber, polyethylene-graft-maleic anhydride (PE-g-MA), both with and without nanoclay (NC). The results showed that the addition of NC into WPC slightly decreased tensile strength due to low surface interactions. However, tensile modulus had increased from 1471 to 2001 MPa due to rigid structures of NC. The impact strength of WPC increased from 6.1 to 8.2 kJ/m2 due to exfoliation of NC had improved fiber/nanoclay-matrix interfacial. DSC results showed that only one peak of Tg had observed in both WPC due to miscible blending. The WPC decomposition had slightly affected with NC addition. The cross-section of WPC observed no holes in kenaf/rPE/nanoclay.